Manajemen Kepala Sekolah dalam Menciptakan Iklim Organisasi Kondusif Di SDN Rancamanyar 01 - Deti Rostini; Kakay Karyana; Lufi Ardiana; Raden Dewangga Tresna Erawan; Desemberi Trianugrahwati (Departement of Mathematics Education, 2023)
This research is based on the ability of qualified school principals to improve the quality and progress of schools. The existence of good principal management can make the school a conducive organizational climate. A conducive organizational climate certainly requires a strong role for the principal in planning, organizing, implementing and supervising its management. The purpose of this research is to describe and analyze principal management related to planning, organizing, implementing, and supervising in creating a conducive organizational climate in elementary schools. This research uses a qualitative approach with a case study method. Sources of data in this study are primary data and secondary data. Observations, interviews and documentation were used as data collection techniques in this study. Analysis of the data in this study through steps including data collection, data reduction, data exposure, and drawing conclusions. The research results obtained are the ability of the principal's management in planning a conducive organizational climate at SDN Rancamanyar 01. The ability of the principal's management in organizing a conducive organizational climate at SDN Rancamanyar 01 is in accordance with applicable procedures. In addition, the ability of the principal's management in implementing a conducive organizational climate has been going well and the ability of the principal's management in supervision to create a conducive organizational climate by conducting monitoring and evaluation has also been carried out well. From this, it can be concluded that the management of the school principal can be stated that the head of SDN Rancamanyar 01 has been able to create a conducive organizational climate.